2007
DOI: 10.1016/j.pepi.2007.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of explosive-driven shocks on the natural remanent magnetization and the magnetic properties of rocks

Abstract: Please cite this article as: Gattacceca, J., Lamali, A., Rochette, P., Boustie, M., Berthe, L., The effects of explosive-driven shocks on the natural remanent magnetization and the magnetic properties of rocks,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
99
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(108 citation statements)
references
References 17 publications
(2 reference statements)
7
99
2
Order By: Relevance
“…Gattacceca et al (2007) observed similar changes in AMS for basalt and microdiorite shocked to pressure greater than 10 GPa.…”
Section: Summary and Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Gattacceca et al (2007) observed similar changes in AMS for basalt and microdiorite shocked to pressure greater than 10 GPa.…”
Section: Summary and Discussionsupporting
confidence: 56%
“…Such stress-induced anisotropy has been suggested to be removable by tumbling AF demagnetization (Park et al, 1988). In contrast, the AMS changes recorded at intermediate to high shock pressures may be related to either the fracturing of magnetic grains (Gattacceca et al, 2007) or the formation of lattice defects, such as dislocations. Both mechanisms are consistent with the high stability of the AMS changes against AFD (Fig.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to SRM, a shock event may induce piezoremanent magnetization (PRM) in relatively lower pressure and TRM by heating up to blocking temperatures (e.g. Gattacceca et al 2007). PRM is possibly parallel to the ambient field and effective on lower coercivity part of magnetic minerals (e.g.…”
Section: Remanence Type and Direction Of The Lunar Crust Magnetizationmentioning
confidence: 99%
“…Since direct estimation of shock pressure is difficult, indirect indicators, such as shock-induced brittle and ductile deformation features, mineralogical changes, and polymorphism, are commonly used (e.g., Hörz, 1969;Melosh, 1989;Huffman et al, 1993;Kenkmann et al, 2000Kenkmann et al, , 2014Gattacceca et al, 2007;Nishioka et al, 2007;Nishioka and Funaki, 2008). The indicators are weak or commonly absent when the shock pressures are low, especially ≤3 GPa.…”
Section: Introductionmentioning
confidence: 99%